2003
DOI: 10.1084/jem.20030422
|View full text |Cite
|
Sign up to set email alerts
|

Direct Expansion of Functional CD25+ CD4+ Regulatory T Cells by Antigen-processing Dendritic Cells

Abstract: An important pathway for immune tolerance is provided by thymic-derived CD25+ CD4+ T cells that suppress other CD25− autoimmune disease–inducing T cells. The antigen-presenting cell (APC) requirements for the control of CD25+ CD4+ suppressor T cells remain to be identified, hampering their study in experimental and clinical situations. CD25+ CD4+ T cells are classically anergic, unable to proliferate in response to mitogenic antibodies to the T cell receptor complex. We now find that CD25+ CD4+ T cells can pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

42
686
2
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 795 publications
(742 citation statements)
references
References 54 publications
42
686
2
6
Order By: Relevance
“…Interactions with the microbiota may provide a constant activation of T cells and induce continuous production of IL-2 by nonregulatory T cells as originally proposed by Papiernik et al [46]. IL-2 has proven crucial for the expansion and survival of Treg [47,48]. This concept is further supported by the observation that mice deficient of IL-2 develop colitis and autoimmune manifestations [46,[49][50][51].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Interactions with the microbiota may provide a constant activation of T cells and induce continuous production of IL-2 by nonregulatory T cells as originally proposed by Papiernik et al [46]. IL-2 has proven crucial for the expansion and survival of Treg [47,48]. This concept is further supported by the observation that mice deficient of IL-2 develop colitis and autoimmune manifestations [46,[49][50][51].…”
Section: Discussionmentioning
confidence: 89%
“…Studies have shown that TLR-activated DC can reverse Treg anergy, suggesting that this could override suppression and permit protective immunity towards pathogens [52,53]. However, it has been demonstrated that Treg proliferation is transient, that Treg can return to their anergic and suppressive state, and that the proliferation expands the Treg population [47]. Other studies have reported that CD4 + T cells [54] and CD4 + CD25 + express several TLR and can be activated by LPS [55], which suggests a more direct influence of bacteria or bacterial products on Treg.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the possible role of DC in sustaining T reg proliferation [10] we tested whether BM-derived DC from CD40KO differ from those of BALB/c mice in such function. T reg proliferation was 60% less when Ab to CD3 was presented by mature DC from CD40KO than wt mice (Fig.…”
Section: Lacking Cd40 Are Defective In Sustaining T Reg Proliferationmentioning
confidence: 99%
“…In agreement with this, importantly, we showed that such a defect in the MRL/lpr DC function could be fully restored by exogenous IL-2. IL-2 has been shown to be essential in the Treg induction by DC in various systems, both in an antigen-specific and nonspecific manner [50][51][52], although different findings were also reported [53]. It remains to be determined as to whether the T cells upon stimulation by the DC [51], or DC themselves, or both of the cell types together, could be the direct source of IL-2.…”
Section: Discussionmentioning
confidence: 95%
“…IL-2 has been shown to be essential in the Treg induction by DC in various systems, both in an antigen-specific and nonspecific manner [50][51][52], although different findings were also reported [53]. It remains to be determined as to whether the T cells upon stimulation by the DC [51], or DC themselves, or both of the cell types together, could be the direct source of IL-2. In addition, DC can also produce IL-15 [48,49,54], but whether or not and how this cytokine is involved in Treg induction is still to be clarified [53,55].…”
Section: Discussionmentioning
confidence: 95%